The Impact of Using Cartoon Movie To Increase Vocabulary Mastery In Elementary School - Layya Aisah Al Hasan; Godefridus Bali Geroda; Widi Syatia Pane (Inquest Journal, 2023)
Background: Learning vocabulary for elementary school students requires a kind of special treatment so that students can pay more attention and focus on learning. Cartoon movie is one of the media that can be used for learning activities. Methodology: This research is an experimental type with a one group pretest-posttest design and data analysis techniques using the Paired Sample T Test as well as using cartoon movie “Dora the Explorer” as a treatment to find out whether there was an increase in students' vocabulary mastery or not. Findings: The results of this study showed an increase in students' vocabulary mastery from the results of the data obtained by the researcher from the pre-test and post-test scores after being given treatment. Conclusion: The researcher concluded that cartoon movies can be used as learning media to improve vocabulary skills in student because it is evident from the result of the tests and treatments given that there is a significant increase in scores. in the first meeting there was an increase in the average pre-test score from 65.50 to 82.00 in the post-test average score, and at the second meeting there was also an increase in the average score from 42.50 in the pre-test results to 77.50 in the post-test results. Originality: Cartoons are characterized by bright colors, varying degrees of movement, simple themes or messages for children to understand, shorter duration, variety of sounds, and other stimuli that appeal to children. The vocabulary contained in the cartoon is also simple which will make it easier for children to remember the vocabulary.